Direct comparison of non-osteoarthritic and osteoarthritic synovial fluid-induced intracellular chondrocyte signaling and phenotype changes. Issue 1 (January 2023) - Housmans, B.A.C.; van den Akker, G.G.H.; Neefjes, M.; Timur, U.T.; Cremers, A.; Peffers, M.J.; Caron, M.M.J.; van Rhijn, L.W.; Emans, P.J.; Boymans, T.A.E.J.; Feczko, P.Z.; van der Kraan, P.M.; et al.
Summary: Objective: Since the joint microenvironment and tissue homeostasis are highly dependent on synovial fluid, we aimed to compare the essential chondrocyte signaling signatures of non-osteoarthritic vs end-stage osteoarthritic knee synovial fluid. Moreover, we determined the phenotypic consequence of the distinct signaling patterns on articular chondrocytes. Methods: Protein profiling of synovial fluid was performed using antibody arrays. Chondrocyte signaling and phenotypic changes induced by non-osteoarthritic and osteoarthritic synovial fluid were analyzed using a phospho-kinase array, luciferase-based transcription factor activity assays, and RT-qPCR. The origin of osteoarthritic synovial fluid signaling was evaluated by comparing the signaling responses of conditioned media from cartilage, synovium, infrapatellar fat pad and meniscus. Osteoarthritic synovial fluid induced pathway–phenotype relationships were evaluated using pharmacological inhibitors. Results: Compared to non-osteoarthritic synovial fluid, osteoarthritic synovial fluid was enriched in cytokines, chemokines and growth factors that provoked differential MAPK, AKT, NFκB and cell cycle signaling in chondrocytes. Functional pathway analysis confirmed increased activity of these signaling events upon osteoarthritic synovial fluid stimulation. Tissue secretomes of osteoarthritic cartilage, synovium, infrapatellar fat pad and meniscus activated several inflammatory signaling routes. Furthermore, the distinct pathway signatures of osteoarthritic synovial fluid led to accelerated chondrocyte dedifferentiation via MAPK/ERK signaling, increased chondrocyte fibrosis through MAPK/JNK and PI3 K/AKT activation, an elevated inflammatory response mediated by cPKC/NFκB, production of extracellular matrix-degrading enzymes by MAPK/p38 and PI3 K/AKT routes, and enabling of chondrocyte proliferation. Conclusion: This study provides the first mechanistic comparison between non-osteoarthritic and osteoarthritic synovial fluid, highlighting MAPKs, cPKC/NFκB and PI3 K/AKT as crucial OA-associated intracellular signaling routes.